Development of Incubator Analyzer Based on Computer with Temperature And Humidity Parameters - Syarifatul Ainiyah; Dwi Herry Andayani; Andjar Pundji; Triwiyanto Triwiyanto; M Shaib (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
By opening and closing an infant incubator window during calibration, it can cause temperature leaks, such as a decrease in the incubator temperature. The purpose of this study is to develop an incubator analyzer, in which the data can be recorded to a computer for temperature and humidity parameters based on Bluetooth communication. Whereas for a non-computer displayed, the information is shown on a 20x4 LCD with SD Card storage. The contribution of this study is to calibrate baby incubators without a decrease in temperature, and also, the system can monitor the data collection at a maximum distance of 10 meters. In order to avoid decreasing in temperature, the module is displayed on the Personal Computer and storage on the SD Card. Incubator Analyzer is designed to simplify and facilitate calibration with temperature parameters at 5 points using a DS18B20 sensor, mat temperature using a K type thermocouple and humidity using a DHT22 sensor. In the temperature setting of 34 C and 36 C, the average error result is -4.87% for DS18B20, -7.39% error for mattress temperature, and -24.80% for humidity sensor. Data generated from comparisons using the INCU II test conclude that the measurement results between modules and standard devices have significant differences in values. The results of this study can be implemented on baby incubators to increase the appropriateness of the device.